Outcome of Rhegmetogenous Retinal Detachment Surgery in Uncomplicated Pseudophakic Eyes - A. Fattah Memon, P.S. Mahar, A. Qadeem Soomro (Pakistan Journal of Ophthalmology, 2018)
Purpose: To assess the anatomical reattachment and visual outcome in pseudophakic patients with rhegmatogenous retinal detachment (RD) after pars plana vitrectomy (PPV). Material and Methods: This case series study was conducted at Isra Postgraduate Institute of Ophthalmology from July 2004 to June 2006. Thirty five eyes of 35 patients developed rhegmatogenous retinal detachment after uncomplicated extra capsular cataract extraction (ECCE) with intraocular lens (IOL) implant. All eyes went under 3 – port PPV with air fluid exchange and injection of silicon oil (SO) for internal tamponade. Results: There were 27 male (77%) and 8 female (23%) with 3.5:1 male to female ratio. Twenty eyes (27%) had total, while 15 eyes (43%) had subtotal RD. The mean duration at which, retinal detachment was noticed after cataract surgery was 128 ± 243 days. At mean follow up of 1 year, improvement in visual acuity was seen in 23 (65%) eyes, 3 (9%) eyes showed no improvement and 9 (26%) eyes had deterioration in vision. The anatomic reattachment was registered in 31 (89%) eyes. Conclusion: Our results suggest that 3-port PPV with use of SO is an effective procedure resulting in high proportion of cases showing successful anatomic reattachment and visual improvement.